Using Stata for Principles of econometrics, fourth edition - Adkins, Lee C. (John Wiley & Sons, 2011)
Using Stata for Principles of Econometrics is a cutting edge text which incorporates the capabilities of Stata software to practically apply the principles of econometrics. Readers will learn how to apply basic econometric tools and the Stata software to estimation, inference and forecasting in the context of real world economic problems. In order to make concepts more accessible, it also offers lucid descriptions of techniques as well as appropriate applications to today's situations. Along the way, readers will find introductions to simple economic models and questions to enhance critical thinking.